Predicting Drug–Drug Interactions Between Rifampicin and Long-Acting Cabotegravir and Rilpivirine Using Physiologically Based Pharmacokinetic Modeling. (19th December 2018) - Rajoli, Rajith K R; Curley, Paul; Chiong, Justin; Back, David; Flexner, Charles; Owen, Andrew; Siccardi, Marco
Abstract: Background: Cabotegravir and rilpivirine are 2 long-acting (LA) antiretrovirals that can be administered intramuscularly; their interaction with rifampicin, a first-line antituberculosis agent, has not been investigated. The aim of this study was to simulate and predict drug–drug interactions (DDIs) between these LA antiretroviral agents and rifampicin using physiologically based pharmacokinetic (PBPK) modeling. Methods: The designed PBPK models were qualified (according to European Medicines Agency guidelines) against observed data for oral formulations of cabotegravir, rilpivirine, and rifampicin. Induction potential of rifampicin was also qualified by comparing the DDI between oral cabotegravir and oral rilpivirine with rifampicin. Qualified PBPK models were utilized for pharmacokinetic prediction of DDIs. Results: PBPK models predicted a reduction in both area under the curve (AUC0-28 days ) and trough concentration (Ctrough, 28th day ) of LA cabotegravir of 41%–46% for the first maintenance dose coadministered with 600 mg once-daily oral rifampicin. Rilpivirine concentrations were predicted to decrease by 82% for both AUC0-28 days and Ctrough, 28th day following the first maintenance dose when coadministered with rifampicin. Conclusions: The developed PBPK models predicted the theoretical effect of rifampicin on cabotegravir and rilpivirine LA intramuscular formulations. According to these simulations, it is likely that coadministration of rifampicin with these LA formulations will result in subtherapeutic concentrations of both drugs. Abstract : This article highlights the use of physiologically based pharmacokinetic models for the evaluation of drug–drug interaction magnitude between long-acting antiretroviral formulations of cabotegravir and rilpivirine coadministered with oral rifampicin in an adult population.